BASIS TEOLOGIS DAKWAH EKOLOGIS - Fata, Ahmad Khoirul (Jurnal Bimas Islam, 2017)
The damage of nature is caused by human activities. That makes any disasters that falling on human. The ecological crisis must be solved by religious people to avoide human existence threat. In this point, dakwah as a attempt to make the human condition better than before, must enter to this scope. Ecological dakwah is transformation of human view on the nature, from anthropocentric paradigm to islamic paradigm. The aim of this alterationi show human can make their treatment to nature better than before. Human stop exploitation of natureand make a harmonic relation with the nature. There are three islamic doctrines to build the ecological dakwah: nature and human are creation of Allah, natureand human are signs of existence of Allah, and human are chaliph of Allah in theworld.              Kerusakan alam yang terjadi akibat perilaku manusia, menyebabkan berbagai bencana alam yang menimpa manusia. Krisis ekologi tersebut harus segera ditangani kaum agamawan agar tidak mengancam eksistensi manusia. Di sinilah dakwah sebagai upaya mengubah kondisi manusia menjadi lebih baik harus segera masuk ke ruang ekologis ini. Dakwah ekologis dimaksudkan untuk mengubah paradigma manusia dari antroposentrisme menuju ke paradigma yang islami dalam menjalin hubungan dengan alam. Dengan perubahan itu diharapkan perlakuan manusia terhadap alam tidak lagi eksploitatif sehingga alam tetap terjaga kelestariannya. Ada beberapa doktrin Islam yang bisa menjadi landasan bagi dakwah model ini, yaitu: konsep alam dan manusia sebagai makhluk Allah, alam dan manusia sebagai ayat Allah, dan manusia sebagai khalifah Allah di bumi.